Experiences and Stressors of Parents of Trans and Gender-Diverse Youth in Clinical Care from Trans Youth CAN!. Issue 2 (8th March 2022) - Pullen Sansfaçon, Annie; Temple Newhook, Julia; Douglas, Laura; Gotovac, Sandra; Raiche, Joe; Speechley, Kathy Nixon; Lawson, Margaret L; Bauer, Greta R
Abstract: Parents of trans and gender-diverse youth can experience challenges navigating gender-affirming (GA) care such as stigma, transphobia, and lack of support. There is little information available about stressors, worries, and positive feelings of parents as they try to support their youth accessing GA care. This article presents baseline survey data on experiences and stressors of 160 parents/caregivers in the Trans Youth CAN! cohort study, which examined medical, social, and family outcomes in youth age 16 years or younger considering puberty blockers or GA hormones. Data were collected at 10 Canadian gender clinics. Authors report on participating parents' characteristics, levels of support toward youth, stressors, worries, concerns, and positive feelings related to youth's gender. Most parent participants were White (85.1 percent), female (85.1 percent), birth or adoptive parents (96.1 percent), and reported strong support for youth's gender. Participants' concerns included their youth facing rejection (81.9 percent), generalized transphobia (74.6 percent), or encountering violence (76.4 percent). Parents also reported positive feelings about seeing their youth grow more confident. Most parental worries and stressors were situated outside the family, reflecting the systemic discrimination faced by youth and their families. Social workers could address these by developing systems-focused interventions and by further taking into account intersectional health disparities.